2021
DOI: 10.1016/j.xcrm.2021.100281
|View full text |Cite
|
Sign up to set email alerts
|

β-sitosterol reduces anxiety and synergizes with established anxiolytic drugs in mice

Abstract: Highlights d In silico screen identifies b-sitosterol as a candidate anxiolytic drug d b-sitosterol is anxiolytic in both naive and chronically stressed mice d b-sitosterol alters the expression of immediate early genes d Sub-efficacious doses of b-sitosterol and fluoxetine synergize when combined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Meanwhile, β-sitosterol exhibits antidepressant and anxiolytic effects (179) (273), possibly mediated through serotonergic, GABAergic and dopaminergic mechanisms. Furthermore, phytosterols modulate the activity of endogenous steroid receptors.…”
Section: Phytosterol Impact On the Microbiota-gut-brain Axismentioning
confidence: 99%
“…Meanwhile, β-sitosterol exhibits antidepressant and anxiolytic effects (179) (273), possibly mediated through serotonergic, GABAergic and dopaminergic mechanisms. Furthermore, phytosterols modulate the activity of endogenous steroid receptors.…”
Section: Phytosterol Impact On the Microbiota-gut-brain Axismentioning
confidence: 99%
“…Previous studies have shown that increased time spent in the central area in the OFT, light compartment in the LDT and open arms of the EPMT, and less time of latency to eat is one indicator of the effectiveness of anti-anxiety drugs. 39,40 Our study found that compared with NS, administration of OD-CDs for 7 days resulted in significant anti-anxiety effects, close in potency to diazepam, a typical benzodiazepine drug that is often used in the animal model of anxiety as a positive control drug and has a clinically stable antianxiety effect. 41,42 DZP did not have sedative effects at 2 mg/kg.…”
Section: Discussionmentioning
confidence: 80%
“…LC-MS found that all these molecules were present in the aqueous extract of WDD we prepared. After a systematic literature search, naringenin, 56 quercetin, 57 , 58 glabridin, 59 beta-sitosterol, 60 luteolin 61 , 62 of them was the candidate molecule for anxiety. Among them, the anxiolytic effects of quercetin, luteolin and narigenin are closely related to the inhibition of inflammatory response, suggesting that inhibition of inflammatory response may be the potential mechanism of Wendan Decoction in treating GAD.…”
Section: Discussionmentioning
confidence: 99%